Network structure and fragmentation of the Argentinean interbank markets - Pedro Elosegui; Federico D. Forte; Gabriel Montes-Rojas (Banco Central de la República Argentina (BCRA), Investigaciones Económicas (ie), 2021)
This paper studies the network structure and fragmentation of the Argentine interbank market. Both the unsecured (CALL) and the secured (REPO) markets are examined. The aim of this study is to understand their actual fragmentation, as well as its potential implications for monetary policy and financial stability. Applying network analysis, different underlying segments within the market are identified. We approximate the theoretical distribution that better fits the empirical degree distribution of the interbank loan networks. Based on standard topological metrics, it is found that, although the secured market has less participants, its nodes are more densely connected than in the unsecured market. In addition, the interrelationships in the unsecured market are less stable, as it was witnessed during the 2018 currency crisis, making its structure more volatile and vulnerable to negative shocks. The analysis identifies two "hidden" underlying sub-networks within the REPO market: one based on the transactions collateralized by Treasury bonds (REPO-T) and other based on the operations collateralized by Central Bank (CB) securities (REPO-CB). The connectivity indicators were significantly more stable in the REPO-T market than in the REPO-CB segment. The changes in monetary policy stance and monetary conditions seem to have a substantially smaller impact in former than in the latter "sub-market". Hence, the connectivity levels within the REPO-T market remain relatively unaffected by the (in some period pronounced) swings in the other segment of the market. These results have implications in terms of the interpretation of the interest rates that arise from these markets.
Keywords: C2; C12; G21; G28; 330; network analysis; interbank market; fragmentation; central bank; monetary policy; Argentina